Quantum probability and applications V: proceedings of the Fourth Workshop, held in Heidelberg, FRG, Sept. 26–30, 1988 - Accardi, Luigi (Lecture notes in mathematics, 1990)
These proceedings of the workshop on quantum probability held in Heidelberg, September 26-30, 1988 contains a representative selection of research articles on quantum stochastic processes, quantum stochastic calculus, quantum noise, geometry, quantum probability, quantum central limit theorems and quantum statistical mechanics